Updating conservation metagenomics on the gut microbiome of threatened mammals - Le Wang; Guangping Huang; Guoliang Li; Shibin Yuan; Fuwen Wei (iScience, 2025)
Summary: During the past two decades, much work has characterized the composition and function of the gut microbiome on diverse wildlife in the framework of conservation metagenomics. While promising for conservation, translating theory into practice remains challenging and requires progress. Here, we summarize the progress of gut microbiomes of threatened mammals from ecology and evolution to conservation practice, and propose an integrative framework for future conservation metagenomics within which multi-dimension, multi-scale, multi-technology, and multi-omics can be comprehensively considered to advance our understanding of the patterns and underpinnings of wildlife gut microbiomes. We also propose microbiome banking to archive endangered species’ biological information and microbial entities. Moreover, a reference framework for cutting-edge gut metagenomics research on the giant panda is outlined, demonstrating the field’s potential. Finally, while microbiome manipulation shows promise, it remains experimental—demanding stringent safety protocols, vigilant oversight, and thorough risk assessment to ensure responsible application.